Association between activities of daily living and depressive symptoms among older adults in China: evidence from the CHARLS - Haixia Liu; Yang Ma; Lin Lin; Zekun Sun; Zeyu Li; Xinxin Jiang (Frontiers Media S.A., 2023)
ObjectiveThe limitation of activities of daily living (ADL) affects the mental health of older adults. We distinguished activities of daily living into basic activities of daily living (BADL) and instrumental activities of daily living (IADL) and aimed to explore the relationship between the two limitations and depressive symptoms among Chinese older adults by using nationally representative cross-sectional data.MethodsData from the China Health and Retirement Longitudinal Study (CHARLS, wave 4) were used, and 9,789 older adults aged 60 years and above were screened. The 10-item Center for Epidemiologic Studies Depression (CES-D-10) scale was used to measure the depressive symptoms of older adults, and a 12-item scale for ADL was used to estimate functional limitations. Generalized linear mixed-effect models were employed to examine the relationship between BADL/IADL and depressive symptoms among older adults.ResultsThe prevalence of high-risk depression among older adults was 43.5%, and the rates of limitation in BADL and IADL were 19.02 and 25.29%, respectively. The prevalence of high-risk depression significantly differed among subgroups of smoking, drinking, chronic diseases, duration of sleep, having social activities or not, and the type of medical insurance. Older adults with limited BADL or IADL were at a higher risk of depression than those without limitations of BADL or IADL; BADL (OR-adjusted = 2.71; 95% CI: 2.40-3.06) and IADL (OR-adjusted = 2.68; 95% CI: 2.41-2.98) had various influences on the risk of depression in older adults.ConclusionADL was a related factor in the risk of depression among older adults in China. BADL and IADL had different effects on the risk of depression, suggesting that older adults with physical function limitations might be more likely to suffer from depression.